Ultraviolet curing adhesive for manufacturing optical fiber ring of optical fiber gyroscope with framework
By providing a specific composition of skeleton fiber gyro fiber surrounding UV curing adhesive, the problem that existing adhesives cannot match the fiber performance is solved, and higher accuracy and reliability are achieved.
Patent Information
- Application Number
- CN202411843082.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-11
AI Technical Summary
The existing ultraviolet curing glue cannot match the optical fiber and cannot meet the application environment requirements of fiber gyroscopes, especially in terms of temperature and vibration.
A UV curing glue for skeleton fiber gyro fiber surround preparation is provided, and the composition includes a first polyurethane acrylate, a second polyurethane acrylate, a reactive diluent and a photoinitiator. The performance of the adhesive is optimized through a specific mass ratio and preparation step.
The adhesive has a small thermal expansion coefficient, a low elastic modulus, a high glass transition temperature and a small curing shrinkage rate, which can match the performance of the optical fiber and improve the accuracy and reliability of the optical fiber gyroscope.
Smart Images

Figure BDA0005188389910000091 
Figure BDA0005188389910000092 
Figure BDA0005188389910000101
Abstract
Description
Technical Field
[0001] The invention relates to an adhesive for optical fiber, in particular to an ultraviolet light curing adhesive for optical fiber surrounding of a skeleton optical fiber gyroscope. Background Art
[0002] Fiber optic gyroscopes can be divided into three categories according to their optical working principles: interferometric fiber optic gyroscopes, resonant fiber optic gyroscopes, and stimulated Brillouin scattering fiber optic gyroscopes. Among them, interferometric fiber optic gyroscope technology has been fully mature and industrialized, while resonant fiber optic gyroscopes and stimulated Brillouin scattering fiber optic gyroscopes are still in the basic research stage, and there are still many issues that need to be further explored.
[0003] Among them, the fiber ring in the interferometric fiber gyroscope is a component that is sensitive to the sagnac phase difference between two counter-propagating light waves caused by the input angular velocity. It is the measuring element and sensing core of the fiber optic gyroscope, and its quality directly affects the accuracy of the fiber optic gyroscope.
[0004] Fiber optic rings are divided into skeleton fiber optic rings and skeleton-free fiber optic rings. Skeleton fiber optic rings are composed of optical fiber, ring winding glue and a skeleton (usually an aluminum skeleton). The optical fiber is wound on the skeleton, the ring winding glue is brushed on it, and it is installed in the fiber optic gyroscope after curing and forming. Skeleton-free fiber optic rings are made by winding the optical fiber on a tooling, removing the tooling after curing and forming, and obtaining a skeleton-free fiber optic ring, which is then installed in the fiber optic gyroscope.
[0005] At present, there is no adhesive specifically used in the field of fiber optic gyroscopes at home and abroad. Although the common UV curing glue or thermosetting glue on the market can meet the process requirements of fiber optic rings, its performance cannot fully match the optical fiber, resulting in failure to meet the application environment requirements of fiber optic gyroscopes. The ring adhesive of skeleton fiber optic rings should have the following characteristics: ① Appropriate viscosity and long application period, which is convenient for brushing glue operation; ② Small curing shrinkage, which can reduce the internal stress of the fiber optic ring and improve temperature performance; ③ The glass transition temperature is not within the working range of the fiber optic gyroscope (-40℃~+60℃); ④ Good adhesion to metal to prevent gaps between the fiber optic ring and the skeleton. However, the current UV curing glue cannot meet the above requirements. Therefore, there is an urgent need for an adhesive that not only meets the above requirements, but also has good matching with the optical fiber and can better adapt to the temperature and vibration requirements of the fiber optic gyroscope. Summary of the invention
[0006] The purpose of the present invention is to solve the problem that the UV curing adhesive in the prior art cannot match the optical fiber and cannot meet the application environment requirements of the optical fiber gyroscope, and to provide a UV curing adhesive for optical fiber surrounding of a skeleton optical fiber gyroscope.
[0007] To achieve the above objectives, the technical solutions provided by the present invention are as follows:
[0008] A UV curing adhesive for fiber wrapping of a skeleton fiber optic gyroscope, which is special in that it comprises a first polyurethane acrylate, a second polyurethane acrylate, a reactive diluent, and a photoinitiator, and the mass ratio thereof is: (35-60): (80-100): (30-50): (4-6); the first polyurethane acrylate and the second polyurethane acrylate are both aliphatic polyurethane acrylates; the first polyurethane acrylate has a functionality of 2-4, and a glass transition temperature of not less than 20°C; the second polyurethane acrylate has a functionality of 2, and a glass transition temperature of not more than -45°C; the reactive diluent The initiator is one or more of neopentyl glycol diacrylate, propoxylated neopentyl glycol diacrylate, tripropylene glycol diacrylate, diethylene glycol diacrylate, methacrylate laurate, isodecyl acrylate, isooctyl acrylate, ethoxyethoxy acrylate, and lauric acrylate; the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxy-cyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzophenone, isopropylthioxanthone, and 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone.
[0009] Further, the functionality of the first polyurethane acrylate is 2 to 3, and the glass transition temperature is not less than 40°C and not more than 85°C;
[0010] The active diluent is one or more of neopentyl glycol diacrylate, tripropylene glycol diacrylate, propoxylated neopentyl glycol diacrylate, methacrylate laurate, and acrylate laurate;
[0011] The photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxy-cyclohexyl benzophenone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0012] Furthermore, the mass ratio of the first polyurethane acrylate, the second polyurethane acrylate, the reactive diluent and the photoinitiator is 50:90:40:5; wherein the reactive diluent is neopentyl glycol diacrylate and lauric methacrylate in a mass ratio of 3:1, and the photoinitiator is 1-hydroxy-cyclohexyl benzophenone.
[0013] Further, the second polyurethane acrylate is prepared by the following steps:
[0014] S1. Add 0.2 mol to 0.3 mol of diisocyanate and 0.2 g to 0.25 g of dibutyltin laurate catalyst into a reactor, raise the temperature to 40°C to 50°C, dropwise add 0.1 mol to 0.15 mol of polypropylene glycol, react for 2 to 3 hours, take a sample from the reactor to determine the isocyanate value, and when the measured value reaches the theoretical isocyanate value of the complete reaction of polypropylene glycol, proceed to step S2. If not, continue the reaction until the value is reached;
[0015] S2. Add 0.2 mol to 0.3 mol of methyl acrylate, 0.2 g to 0.25 g of dibutyltin laurate and 0.2 g to 0.25 g of p-hydroxyanisole into the reactor, raise the temperature to 70°C to 80°C, react for 2.5 to 3.5 hours, take samples every 30 minutes to measure the isocyanate value, terminate the reaction when the measured value is zero, and obtain the second polyurethane acrylate.
[0016] Further, in step S2, the methyl acrylate is obtained by purifying and removing water from the industrial monomer methyl acrylate, specifically:
[0017] The industrial monomer methyl acrylate is placed in a separatory funnel, washed with a sodium hydroxide solution with a mass fraction of 5% to 6% for 3 to 4 times, the sodium hydroxide solution is removed to leave the industrial monomer methyl acrylate, and then the industrial monomer methyl acrylate is washed with distilled water, the volume of the distilled water is 2 / 5 of the industrial monomer, and the washing is repeated several times until the pH value is 7.0; the water layer is removed, and anhydrous sodium sulfate is added, the amount of anhydrous sodium sulfate is 5% to 6% of the mass of the industrial monomer methyl acrylate, and after sufficient shaking, it is placed in a refrigerator and left to stand for at least 3 days; the treated industrial monomer methyl acrylate is subjected to reduced pressure distillation using a rotary evaporator, and the obtained fraction is the methyl acrylate.
[0018] Further, in step S1, the polypropylene glycol is polypropylene glycol that has been subjected to a purification and water removal treatment, specifically:
[0019] The polypropylene glycol was vacuum dehydrated at 110°C to 120°C and a vacuum degree of -0.1 MPa for 2 hours.
[0020] Further, in step S1, the temperature is raised to 45°C to 50°C;
[0021] In step S2, the temperature is raised to 70°C to 75°C.
[0022] Further, in step S1, the amount of toluene diisocyanate is 0.2 mol, the amount of dibutyltin laurate is 0.2 g, the temperature is raised to 45° C., the amount of polypropylene glycol is 0.1 mol, the molecular weight is 3000, and after the reaction time is 2 h, sampling is performed to determine the isocyanate value;
[0023] In step S2, 0.2 mol of methyl acrylate, 0.2 g of dibutyltin laurate and 0.2 g of p-hydroxyanisole are added, and the temperature is raised to 75° C. for reaction; after reacting for 3 hours, samples are taken every 30 minutes to measure the isocyanate value, and the reaction is terminated when the measured value is zero.
[0024] Beneficial effects of the present invention:
[0025] 1. The UV curing adhesive for fiber-optic gyroscope with skeleton is an acrylate adhesive, comprising a first polyurethane acrylate, a second polyurethane acrylate, a reactive diluent and a photoinitiator, and its thermal expansion coefficient is less than 200×10 -6 / ℃ (-40℃~60℃), elastic modulus is less than 80MPa (25℃), glass transition temperature is greater than 60℃, curing shrinkage is less than 6%, the glass transition temperature avoids the working range of the fiber optic gyroscope, and the curing shrinkage is small.
[0026] 2. The ultraviolet light curing adhesive used for optical fiber surrounding of a skeleton optical fiber gyroscope of the present invention has a small shrinkage after ultraviolet curing. Combined with the sandblasting treatment of the optical fiber ring skeleton, it can avoid the appearance of a gap between the optical fiber ring and the skeleton, and reduce the input axis misalignment angle error of the skeleton optical fiber gyroscope; at the same time, it takes into account the temperature performance and effectively improves the accuracy of the optical fiber gyroscope. DETAILED DESCRIPTION
[0027] Example 1
[0028] The ultraviolet curing glue for optical fiber wrapping of a skeleton optical fiber gyroscope of the present invention is an acrylate adhesive, which comprises a first polyurethane acrylate, a second polyurethane acrylate, an active diluent, and a photoinitiator, and the mass ratio thereof is: (35-60): (80-100): (30-50): (4-6).
[0029] The first polyurethane acrylate is one of aliphatic polyurethane acrylates, with a functionality of 2 to 4 and a glass transition temperature of not less than 20° C., preferably a functionality of 2 to 3, a glass transition temperature of not less than 40° C. and not more than 85° C. The commercially available aliphatic polyurethane acrylates of CN9001NS, CN1543NS, CN8896NS, and CN969 NS produced by Sartomer, and one of aliphatic polyurethane acrylates of DR-U281, DR-U240, DR-U028FS, 6151, 6172-1, 6130B-80, and 611B-85 produced by Changxing can be used.
[0030] The reactive diluent of the present invention can be one or more of neopentyl glycol diacrylate, propoxylated neopentyl glycol diacrylate, tripropylene glycol diacrylate, diethylene glycol diacrylate, methacrylate laurate, isodecyl acrylate, isooctyl acrylate, ethoxyethoxy acrylate, lauric acrylate. Preferably, one or more of neopentyl glycol diacrylate, tripropylene glycol diacrylate, propoxylated neopentyl glycol diacrylate, methacrylate laurate, lauric acrylate.
[0031] The photoinitiator of the present invention can be one or more of 2-hydroxy-2-methyl-1-phenylpropanone (abbreviated as 1173), 1-hydroxy-cyclohexyl benzophenone (abbreviated as 184), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (abbreviated as TPO), benzophenone (abbreviated as BP), isopropylthioxanthone (abbreviated as ITX), 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone (abbreviated as 907). Preferably, one or more of 1173, 184 and TPO are selected.
[0032] The second polyurethane acrylate is an aliphatic polyurethane acrylate having a functionality of 2 and a glass transition temperature of not greater than -45°C. It is prepared by the following steps:
[0033] Step 1: Raw material purification, dehydration and preparation
[0034] Step 1.1, purifying the purchased raw material isocyanate. In this embodiment, the isocyanate purification method disclosed in the Chinese patent publication number CN 114026064A is preferred;
[0035] Step 1.2, preparation of methyl acrylate (HEA): Take a 500ml separatory funnel, add 300ml of industrial monomer methyl acrylate to it, wash it 3 times with the prepared sodium hydroxide solution (mass fraction of 5%), remove the sodium hydroxide solution below the separatory funnel, and leave the industrial monomer methyl acrylate. Then wash the industrial monomer methyl acrylate with about 120ml of distilled water, and wash it repeatedly several times until the pH is 7.0. Remove the water layer, and then add anhydrous sodium sulfate to the separatory funnel. The amount of anhydrous sodium sulfate is 5% of the mass of the industrial monomer methyl acrylate. After fully shaking, place it in the refrigerator and let it stand for at least 3 days. The treated industrial monomer methyl acrylate is distilled under reduced pressure on a rotary evaporator, and the obtained fraction is the pure product of methyl acrylate, which is stored in a refrigerator.
[0036] Step 1.3, vacuum dehydrating the polypropylene glycol at 110° C. to 120° C. and a vacuum degree of -0.1 MPa for 2 hours. If the water content is high, molecular sieves or the like can be added for physical water absorption.
[0037] Step 2: Synthesis of polyurethane acrylate
[0038] Step 2.1, add 0.2 mol of diisocyanate and 0.2 g of dibutyltin laurate (DBTDL) into the reactor, heat to 40°C to 50°C, slowly drop 0.1 mol of polypropylene glycol, react for 2 hours, take a sample to measure the isocyanate value (NCO value), when the measured value reaches the theoretical NCO value of PPG complete reaction, the reaction ends, if not, continue the reaction until the value is reached. The reaction temperature is preferably 45°C to 50°C. Among them, dibutyltin laurate is used as a catalyst.
[0039] Step 2.2, add 0.2molHEA, 0.2gDBTDL and 0.2g p-hydroxyanisole (MEHQ) to the reactor, and heat to 70°C to 80°C for reaction. After 2.5 to 3.5h of reaction, sample and measure the NCO value every 30min, and discharge the material when the measured value is zero to obtain the second polyurethane acrylate. The reaction temperature is preferably 70°C to 75°C. DBTDL is used as a catalyst and p-hydroxyanisole is used as an inhibitor.
[0040] Among them, polypropylene glycol (PPG) can be commercially available industrial grade PPG (M n =2000), PPG(M n =3000), PPG(M n =4000), PPG(M n =6000), PPG(M n =8000). PPG (M n =3000), PPG(M n =4000) and PPG(M n =6000).
[0041] The diisocyanate can be commercially available industrial grade isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), xylylene diisocyanate (XDI), etc. produced by Bayer. Preferably, one of IPDI, HDI and TDI is used.
[0042] In this embodiment, the second polyurethane acrylate is used to prepare a UV curable adhesive for fiber optic gyroscope with skeleton. Specifically, 50 parts by weight of the first polyurethane acrylate (CN9001NS), 90 parts by weight of the second polyurethane acrylate, 30 parts by weight of neopentyl glycol diacrylate, 10 parts by weight of methacrylate laurate and 5 parts by weight of photoinitiator 184 are mixed and stirred evenly, and then vacuumed for winding. The second polyurethane acrylate is synthesized by the following steps:
[0043] 0.2 mol of toluene diisocyanate (TDI) and 0.2 g of DBTDL were added into the reactor, the temperature was raised to 45°C, and 0.1 mol of polypropylene glycol (PPG, M n =3000), after 2 hours of reaction, take a sample to measure the isocyanate value (NCO value) when the measured value reaches the NCO value of PPG complete reaction in theory.
[0044] Then, 0.2 mol of HEA, 0.2 g of DBTDL and 0.2 g of MEHQ were added and the temperature was raised to 70° C. After reacting for 3.5 hours, samples were taken every 30 minutes to measure the NCO value. When the measured value was zero, the reaction was terminated to obtain the second polyurethane acrylate.
[0045] Example 2
[0046] The present invention discloses a UV curing adhesive for fiber optic gyroscope with skeleton for fiber optic winding, comprising 35 parts by weight of a first polyurethane acrylate (6151), 100 parts by weight of a second polyurethane acrylate, 35 parts by weight of propoxylated neopentyl glycol diacrylate, 10 parts by weight of lauric acrylate, and 5 parts by weight of a photoinitiator 1173. The mixture is stirred evenly, and then vacuumed to be wound around the ring. The specific method for synthesizing the second polyurethane acrylate is as follows:
[0047] 0.2 mol of TDI and 0.2 g of DBTDL were added into the reactor, the temperature was raised to 45°C, and 0.1 mol of polypropylene glycol (PPG, M n =4000), after 2h of reaction, take a sample to measure the NCO value when the measured value reaches the NCO value of PPG complete reaction in theory.
[0048] Then, 0.2 mol of HEA, 0.2 g of DBTDL and 0.2 g of MEHQ were added, and the temperature was raised to 75° C. After 3 hours of reaction, samples were taken every 30 minutes to measure the NCO value, and the material was discharged when the measured value was zero.
[0049] Example 3
[0050] The present invention discloses a UV curing adhesive for fiber optic ringing of a skeleton fiber optic gyroscope, comprising 40 parts by weight of a first polyurethane acrylate (DR-U281), 90 parts by weight of a second polyurethane acrylate, 30 parts by weight of tripropylene glycol diacrylate, 10 parts by weight of isodecyl acrylate, and 4 parts by weight of a photoinitiator 184. The mixture is stirred evenly, and then vacuumed to be ringed. The specific method for synthesizing the second polyurethane acrylate is as follows:
[0051] 0.2 mol of isophorone diisocyanate (IPDI) and 0.2 g of DBTDL were added into the reactor, the temperature was raised to 45°C, and 0.1 mol of polypropylene glycol (PPG, M n=6000), after 2h of reaction, take a sample to measure the NCO value when the measured value reaches the NCO value of PPG complete reaction in theory.
[0052] Then, 0.2 mol of HEA, 0.2 g of DBTDL and 0.2 g of MEHQ inhibitor were added, and the temperature was raised to 80° C. After 2.5 h of reaction, samples were taken every 30 min to measure the NCO value, and the material was discharged when the measured value was zero.
[0053] [Comparative Example]
[0054] The UV-curing adhesive for optical fiber winding provided by a certain optical fiber manufacturer has a viscosity of 3502 mPa·s (25°C), a modulus of about 1.78 MPa at room temperature, an expansion coefficient of 226 / °C (-40°C to +60°C), a glass transition temperature of -40°C, and a qualified rate of input axis misalignment angle of skeleton optical fiber gyroscopes of 56.8%. The skeleton optical fiber ring is wound with the UV-curing adhesive for optical fiber winding of the skeleton optical fiber gyroscope prepared by the above embodiment of the present invention. The performance indicators of the obtained optical fiber ring are shown in Table 1, and the full-temperature scaling factor of the skeleton optical fiber gyroscope is shown in Table 2. According to statistics, the qualified rate of input axis misalignment angle of the skeleton optical fiber gyroscope prepared by the present invention is 88.7%, which is significantly better than that of a certain optical fiber manufacturer.
[0055] Table 1 Performance indicators of skeleton optical fiber ring (full temperature range: -40℃~+60℃)
[0056]
[0057] Table 2 Full temperature scale factor of skeleton fiber optic gyroscope (full temperature range: -40℃~+60℃)
[0058]
[0059]
Claims
1. A UV curing adhesive for fiber-optic gyroscope with skeleton, characterized in that: The invention comprises a first polyurethane acrylate, a second polyurethane acrylate, a reactive diluent and a photoinitiator, wherein the mass ratio of the first polyurethane acrylate and the second polyurethane acrylate is (35-60): (80-100): (30-50): (4-6); The first polyurethane acrylate and the second polyurethane acrylate are both aliphatic polyurethane acrylates; The first polyurethane acrylate has a functionality of 2 to 4 and a glass transition temperature of not less than 20°C; The second polyurethane acrylate has a functionality of 2 and a glass transition temperature of no greater than -45°C; The active diluent is one or more of neopentyl glycol diacrylate, propoxylated neopentyl glycol diacrylate, tripropylene glycol diacrylate, diethylene glycol diacrylate, methacrylate laurate, isodecyl acrylate, isooctyl acrylate, ethoxyethoxy acrylate, and lauric acrylate; The photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxy-cyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzophenone, isopropylthioxanthone, and 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone.
2. The ultraviolet curing adhesive for fiber-optical gyroscope with skeleton according to claim 1, characterized in that: The first polyurethane acrylate has a functionality of 2 to 3 and a glass transition temperature of not less than 40° C. and not more than 85° C.; The active diluent is one or more of neopentyl glycol diacrylate, tripropylene glycol diacrylate, propoxylated neopentyl glycol diacrylate, methacrylate laurate, and acrylate laurate; The photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxy-cyclohexyl benzophenone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
3. The ultraviolet curing adhesive for fiber-optical gyroscope with skeleton according to claim 2, characterized in that: The mass ratio of the first polyurethane acrylate, the second polyurethane acrylate, the active diluent and the photoinitiator is 50:90:40:5; wherein the active diluent is neopentyl glycol diacrylate and lauric methacrylate in a mass ratio of 3:1, and the photoinitiator is 1-hydroxy-cyclohexyl benzophenone.
4. The ultraviolet curing adhesive for fiber-optical gyroscope with skeleton according to any one of claims 1 to 3, characterized in that: The second polyurethane acrylate is prepared by the following steps: S1. Add 0.2 mol to 0.3 mol of diisocyanate and 0.2 g to 0.25 g of dibutyltin laurate catalyst into a reactor, raise the temperature to 40°C to 50°C, dropwise add 0.1 mol to 0.15 mol of polypropylene glycol, react for 2 to 3 hours, take a sample from the reactor to determine the isocyanate value, and when the measured value reaches the theoretical isocyanate value of the complete reaction of polypropylene glycol, proceed to step S2. If not, continue the reaction until the value is reached; S2. Add 0.2 mol to 0.3 mol of methyl acrylate, 0.2 g to 0.25 g of dibutyltin laurate and 0.2 g to 0.25 g of p-hydroxyanisole into the reactor, raise the temperature to 70°C to 80°C, react for 2.5 h to 3.5 h, take samples every 30 min to measure the isocyanate value, terminate the reaction when the measured value is zero, and obtain the second polyurethane acrylate.
5. The ultraviolet curing adhesive for fiber-optical gyroscope with skeleton according to claim 4, characterized in that: In step S2, the methyl acrylate is obtained by purifying and removing water from the industrial monomer methyl acrylate, specifically: The industrial monomer methyl acrylate is placed in a separatory funnel, washed with a sodium hydroxide solution with a mass fraction of 5% to 6% for 3 to 4 times, the sodium hydroxide solution is removed to leave the industrial monomer methyl acrylate, and then the industrial monomer methyl acrylate is washed with distilled water, the volume of the distilled water is 2 / 5 of the industrial monomer, and the washing is repeated several times until the pH value is 7.0; the water layer is removed, and anhydrous sodium sulfate is added, the amount of anhydrous sodium sulfate is 5% to 6% of the mass of the industrial monomer methyl acrylate, and after sufficient shaking, it is placed in a refrigerator and left to stand for at least 3 days; the treated industrial monomer methyl acrylate is subjected to reduced pressure distillation using a rotary evaporator, and the obtained fraction is the methyl acrylate.
6. The ultraviolet curing adhesive for fiber-optical fiber gyroscope with skeleton according to claim 5, characterized in that: In step S1, the polypropylene glycol is polypropylene glycol that has been subjected to a purification and water removal treatment, specifically: The polypropylene glycol was vacuum dehydrated at 110°C to 120°C and a vacuum degree of -0.1 MPa for 2 hours.
7. The ultraviolet curing adhesive for fiber-optical fiber gyroscope with skeleton according to claim 6, characterized in that: In step S1, the temperature is raised to 45°C to 50°C; In step S2, the temperature is raised to 70°C to 75°C.
8. The ultraviolet curing adhesive for fiber-optical gyroscope with skeleton according to claim 7, characterized in that: In step S1, the dosage of toluene diisocyanate is 0.2 mol, the dosage of dibutyltin laurate is 0.2 g, the temperature is raised to 45° C., the dosage of polypropylene glycol is 0.1 mol, the molecular weight is 3000, and after the reaction time is 2 h, sampling is performed to determine the isocyanate value; In step S2, 0.2 mol of methyl acrylate, 0.2 g of dibutyltin laurate and 0.2 g of p-hydroxyanisole are added, and the temperature is raised to 75° C. for reaction; after reacting for 3 hours, samples are taken every 30 minutes to measure the isocyanate value, and the reaction is terminated when the measured value is zero.
Citation Information
Patent Citations
Method for the purification of isocyanates
CN114026064A